Comparison of real-world outcomes in patients with nonvalvular atrial fibrillation treated with direct oral anticoagulant agents or warfarin. (29th January 2019) - Datar, Manasi; Crivera, Concetta; Rozjabek, Heather; Abbass, Ibrahim M; Xu, Yihua; Pasquale, Margaret K; Schein, Jeff R; Andrews, George A
Abstract: Purpose: To compare patients with atrial fibrillation (AF) initiating direct oral anticoagulants (DOACs) versus warfarin on clinical outcomes including stroke, systemic embolism (SE), bleeding events, and cost of care. Methods: This retrospective observational study used Medicare Advantage Prescription Drug and fully insured commercial claims from the Humana Research Database. Patients with AF who initiated a DOAC or warfarin from January 1, 2012, through September 30, 2015, were included. Date of the first prescription of DOAC or warfarin was the index date. Patients in the DOAC and warfarin groups were matched on propensity scores. Patients were censored at end of enrollment or study period, discontinuation, or switch of index medication. Clinical outcomes were compared in the matched groups using Cox proportional hazards models. Annualized costs and costs adjusted for censoring using Lin's interval method were also compared between the two cohorts. Results: Patients on DOACs had a significantly lower risk of ischemic stroke (hazard ratio [HR], 0.88; 95% confidence interval [CI], 0.79–0.98), hemorrhagic stroke (HR, 0.65; CI, 0.46–0.92), SE (HR, 0.53; 95% CI, 0.43–0.65), and composite outcome of stroke or SE (HR, 0.78; 95% CI, 0.71–0.86) compared with patients on warfarin. Bleeding risk was not statistically significant (HR, 0.85; 95% CI, 0.71–1.01). While annualized pharmacy costs were higher, annualized medical and total costs were lower in the DOAC group compared with the warfarin group. Conclusion: The results of the study indicated that patients on DOACs had lower rates of ischemic stroke, hemorrhagic stroke, SE, and composite outcome of stroke or SE compared with patients on warfarin. No significant differences in bleeding rates between the DOAC and warfarin groups were observed, while total cost of care was lower in the DOAC group.